Cultivating the Value of Identity in Early Childhood through the Introduction of Yogyakarta’s Local Culture - Tumbularani, Tumbularani; Winarti, Winarti; Sakila, Siti Risda (CAKRAWALA DINI: JURNAL PENDIDIKAN ANAK USIA DINI, 2025)
This research discusses the cultivation of the value of identity in early childhood through the introduction of local culture of Yogyakarta at TK Batik PPBI Yogyakarta. Using a qualitative method with a field study approach, data was collected through observation, interviews, and documentation. The results showed that the integration of local culture in learning through daily, co-curricular, and extracurricular activities succeeded in instilling identity values, both regional, national, and individual identities. Children involved in local wisdom-based activities show greater self-confidence, appreciation for culture, and pride in their regional cultural heritage. The implementation of Merdeka Curriculum also supports this approach by providing flexibility for schools in developing culture-based learning. This study revealed that the introduction of Yogyakarta local culture through daily, co-curricular, and extracurricular activities at TK Batik PPBI Yogyakarta successfully instilled identity values regional, national, and individual in early childhood. The impact of this research shows that early introduction to local culture not only strengthens children's identity, but also contributes to cultural preservation in the midst of globalization.